Conjugative IncHI2 plasmid harboring novel class 1 integron mediated dissemination of multidrug resistance genes in Salmonella Typhimurium. (April 2021) - Shang, Daiqi; Zhao, Hang; Xu, Xuebin; Arunachalam, Kannappan; Chang, Jiang; Bai, Ling; Shi, Chunlei
Abstract: Salmonella enterica serovar Typhimurium is one of the most important serovars among nontyphoidal Salmonella . The inappropriate and over usage of antimicrobials in clinical and animal husbandry has increased the prevalence of antimicrobial-resistant Salmonella Typhimurium ( S . Typhimurium). Diverse mobile genetic elements (MGEs) such as plasmids, insertion sequences and integrons also have a crucial role in the rapid dissemination of multidrug resistance (MDR) bacteria. This study aimed to screen and analyze the genetic environment of MGEs carried by S . Typhimurium, and to clarify the multidrug resistance dissemination mechanism in S. Typhimurium. The results showed that, out of 255  S . Typhimurium isolates, 62 isolates, were screened out for the presence of IncHI2 plasmid by PCR amplification, of which 61 isolates were carrying both IS 26 and class 1 integron. All the 61 isolates were resistant to at least one antimicrobial and 58 were MDR. The correlation between plasmids and antimicrobial resistance components was determined by conjugation, antimicrobial susceptibility test, PCR-based replicon typing (PBRT) and S1-PFGE experiment. The results of PBRT revealed that 15 transconjugants harboring two kinds of plasmid incompatibility groups including HI2 and I1. Further, S1-PFGE validated the presence of HI2 plasmid in 13 and I1 plasmid in 2 transconjugants, which was about 200–300 kb and 80–100 kb in size, respectively. Whole genome sequencing revealed that no significant difference ( P  > 0.05) was found at the number of antimicrobial resistance gene categories among 15 donor isolates, and ST34 was the predominant sequence type. Phylogenetic analysis based on the complete plasmid sequences revealed 15 IncHI2 plasmids in this study clustered in two different clades and clustered together with other IncHI2 plasmids isolated from China, suggesting that the prevalence and dissemination of IncHI2 plasmids from diverse sources and regions. Four kinds of IS elements-class 1 integron arrangement patterns were identified in the 15 conjugative IncHI2-plasmids, of which three patterns were characterized to be complex IS 26 -class 1 integron arrangement and the other one was IS 256 -class 1 integron arrangement. Overall, these results suggested that IncHI2 was one of the major plasmid lineages presented in the MDR S . Typhimurium strains. Furthermore, the presence of complex IS elements-class 1 integrons and resistance genes co-located on IncHI2 plasmids contributed to the prevalence and rapid dissemination of multidrug resistance genes in Salmonella . Highlights: 61 of 255  S. Typhimurium isolates were triple-positive for IncHI2, IS 26 and intI1, 95.1% were MDR. 15 triple-positive isolates were fully genome sequenced including IncHI2 plasmid. Phylogenetic analysis showed 15 IncHI2 plasmids clustered into 2 clades. 4 IS-class 1 integron arrangement patterns with diverse MRRs were identified in IncHI2 plasmids.